Acute traumatic posterior fracture dislocation of the elbow in pediatric patients: impact of surgery time and associated fractures on outcome. Issue 5 (September 2016) - Bilgili, Fuat; Dikmen, Goksel; Baş, Ali; Asma, Ali; Batibay, Sefa G.; Şirikçi, Murat; Atalar, Ata Can
Abstract : This study assessed the effect of the time interval from initial injury to surgery and the presence of associated fracture on functional outcomes after acute posterior elbow fracture dislocation. Twenty-six pediatric patients were evaluated with respect to operation time point (within 24 h vs. later) and associated fracture retrospectively. The Mayo Elbow Performance Index (MEPI) score was used to assess functional results. The MEPI score was 91 (80–100) in patients with one associated fracture and 83 (75–95) ( P =0.02) in patients with more than one associated fracture. The MEPI score in patients treated within 24 h was 90.3 (75–95) and in those treated later than 24 h, it was 88.6 (75–100) ( P =0.6). Treatment time (within 24 h vs. later) does not affect outcomes, but increasing numbers of associated injuries affect outcomes negatively. Level of study: Level IV case series.